De l'innovation à un modèle de dynamique innovationnelle en enseignement supérieur - Christelle Lison; Denis Bédard; Chantale Beaucher; Denis Trudelle
To provide quality training to meet expectations and needs of future professionals, many higher education institutions choose to develop instructional or curriculum innovations in undergraduate programs. The goals of this paper are both to define innovation in higher education, particularly in a collective way, and to present the model of innovational dynamics drafted by researchers of the Centre de d'études et de recherche en enseignement supérieur. For this, we consider innovation as a process, characterized by generation, acceptance and implementation of change through new ideas, processes, products or services, and conducted by actors in a collective development. The framework we have elaborated is designed for educational purposes and not technological purposes.